2020
DOI: 10.1002/est2.142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phase change material plates' arrangements on charging and discharging of energy storage in building air free cooling

Abstract: Previous examinations of building air free cooling using phase change material (PCM) plates were numerically conducted for specific arrangements/configurations of PCMs plates. Experimental investigation for models validations and comparison between the different configurations of PCMs are the shortages of these studies. The present research experimentally investigates the effects of the PCM plate's arrangements on the thermal characteristics of the charging and discharging processes. Parallel and staggered arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The vital features of phase change materials are the melting and solidification times as well as the latent heat of fusion. Therefore, the melting and solidification characteristics during the PCM charging and discharging process are investigated in many experimental and numerical research works [28][29][30][31][32]. Abduljalil et al [33] presented an experimental study of PCM melting and solidification in a finned triplex tube heat exchanger to examine the charging process under steady and unsteady conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The vital features of phase change materials are the melting and solidification times as well as the latent heat of fusion. Therefore, the melting and solidification characteristics during the PCM charging and discharging process are investigated in many experimental and numerical research works [28][29][30][31][32]. Abduljalil et al [33] presented an experimental study of PCM melting and solidification in a finned triplex tube heat exchanger to examine the charging process under steady and unsteady conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A transient numerical and experimental study is on heat transfer in a cavity filled with air involving one vertical wall with a PCM is presented by Monero et al 14 It was observed that use of the PCM decreased the heat transfer to the air resulting in better cooling. Recently, Nada et al 15 presented experimental investigation of the effects of the arrangement of PCM plates on the thermal characteristics of the charging and discharging processes to be used for building air cooling. It was observed that the quantity of PCMs plates needed in staggered arrangement is lower than that of parallel arrangement.…”
Section: Introductionmentioning
confidence: 99%